Karl Popper : science and enlightenment - Maxwell, Nicholas, 1937- (UCL Press, 2017)
By exploring and challenging Karl Popper's philosophy of science, Nicholas Maxwell argues for a revolution in academic inquiry to help humanity make progress towards a better, more civilized and enlightened world.